Academics and Practitioners Are Alike and Unlike: The Paradoxes of Academic–Practitioner Relationships. (July 2014) - Bartunek, Jean Marie; Rynes, Sara Lynn
In this essay we challenge standard approaches to the academic–practitioner gap that essentially pit sides against each other, treating them as dichotomous. Instead, we identify and suggest ways of working with such dichotomies to foster research and theory building. We delineate several tensions associated with the gap, including differing logics, time dimensions, communication styles, rigor and relevance, and interests and incentives, and show how such tensions are valuable themselves for research and theorizing. We show that the gap often reflects views of conflicting groups of academics, while practitioners' voices are not always incorporated; thus we add a practitioner's voice to the conversation. We describe the dialectical forces that foster the tensions associated with the gap, including initiatives of national governments, ranking systems, and special issues of journals. We then show how the tensions represent fundamental, unresolvable paradoxes that can be generative of new research and practice if appreciated as such. We suggest several implications for research that build on tensions, dialectics, and paradox. We conclude with a brief reflection about the tensions we experienced while writing this essay and what these might suggest about the importance of academic–practitioner relationships.